2016
DOI: 10.1108/pmm-07-2016-0034
|View full text |Cite
|
Sign up to set email alerts
|

Publication rate of presentation abstracts presented at the Canadian Health Libraries Association (CHLA/ABSC) annual meetings from 2004-2009

Abstract: Purpose: To determine the publication rate of Canadian health sciences librarians, post conference presentation. Discover barriers that prevent librarians from taking conference presentation to full publication. Assess the metrics available to librarians for scholarly output measurement by examining metrics, traditional and altmetrics, of articles resulting from conference presentation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 16 publications
2
6
0
Order By: Relevance
“…A systematic review of medical and health care research found that time was the most frequently reported reason, followed by lack of resources, publication not a goal, low priority, and trouble with coauthors [ 5 ]. These reasons are similar to those reported in the LIS literature; time and not intended for publication were the primary reasons reported by presenters at MLA and CHLA conferences [ 8 , 9 ]. Authors at these conferences also reported that they did not publish because their work was not substantial enough [ 8 , 9 ].…”
Section: Introductionsupporting
confidence: 81%
See 2 more Smart Citations
“…A systematic review of medical and health care research found that time was the most frequently reported reason, followed by lack of resources, publication not a goal, low priority, and trouble with coauthors [ 5 ]. These reasons are similar to those reported in the LIS literature; time and not intended for publication were the primary reasons reported by presenters at MLA and CHLA conferences [ 8 , 9 ]. Authors at these conferences also reported that they did not publish because their work was not substantial enough [ 8 , 9 ].…”
Section: Introductionsupporting
confidence: 81%
“…This ranges from 13% at the Association of College and Research Libraries (ACRL) conference in 1999 to 32% at The International Society for Scientometrics and Informetrics [6,7]. The publication rate for medical library conferences appears to be in-between-28% for Medical Library Association (MLA) conferences in 2002 and 2003 and 32% for Canadian Health Libraries Association (CHLA) conferences between 2004 and 2009 [8,9]. Many factors contribute to authors' decisions on whether or not to turn a conference presentation into a full-text article.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are also numerous articles which describe the level, context, and environment in which librarians conduct their research and scholarship (Harrington & Gerolami, 2014;Pickton, 2016;Shaw & Szwajcer, 2016). Much of the research to date has focused on institutional context.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Much of the research to date has focused on institutional context. Within these articles, authors often address the challenges that librarians face when conducting research and the barriers that may prevent them from being productive researchers (Black & Leysen, 1994;Brown, 2001;Fox, 2007;Kennedy & Brancolini, 2012;Lessick et al, 2016;O'Brien & Cronin, 2016;Powell, Baker & Mika, 2002;Shaw & Szwajcer, 2016;Spring, Doherty, Boyes, & Wilshaw, 2014). Commonly noted challenges and barriers include time constraints, lack of support, and lack of research training or experience.…”
Section: Literature Reviewmentioning
confidence: 99%